KORELASI GURU BERSERTIFIKAT PENDIDIK TERHADAP KOMPETENSI PEDAGOGIK GURU DAN PENINGKATAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Shufa, Naela Khusna Faela; Utaminingsih, Sri; Adji, Tito Pangesti (INOPENDAS: Jurnal Ilmiah Kependidikan, 2024)
The purpose of this study was to analyze the correlation between certified teachers and teacher pedagogical competence and improving the quality of learning at SDN Bintoro 5 Demak. This study used a correlational design and quantitative methodology. To collect data in this study, questionnaires, interviews, and direct observation were used. The collected data were analyzed using descriptive statistical analysis techniques and correlational analysis using Karl Pearson's product moment correlation. The results of this study indicate (1) The results of the Pearson correlation test show a very strong relationship between pedagogical competence and learning quality. The correlation values of 0.92 and 0.88 respectively at a significance level of 1% indicate that teacher certification has a positive and significant relationship with pedagogical competence and improving the quality of learning (2) The level of pedagogical competence of certified teachers is higher than that of uncertified teachers as evidenced by the results of the average frequency measurement of teacher pedagogical competence showing an average of 82.3% with a very good category.